2018
DOI: 10.21608/jssae.2018.36465
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Speciation and Mineral Solid Phases of some Heavy Metals in Sludge - amended Soil

Abstract: Speciation of heavy metals exerts important controls on chemical behavior, solubility, toxicity, adsorption and even physical properties of solutions (Ure and Davidson 2002). In the present study, speciation and mineral-solid phase of Cd, Ni, and Pb in solution of soil prolonged irrigated with sewage effluent were predicted using GEOCHEM model (Sposito and Mattigod (1980) and constructed stability diagrams (Sposito ,1989 andLindsay ,1979).The present data indicate that total contents of all tested metals have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The influences of soil contamination on the activities of Cd 2+ in soils were also investigated in the present study,as shown from the Table (3), pCd 2+ values were 9.08 and 8.09 in the 0-yrs and 100-yrs soil samples, respectively, indicating that the continual use of sewage effluent water in irrigation increased Cd 2+ activity by 9.94 folds than the control soil sample.These results are consistent with results reported by [11] who computed the activity of some metals (M/L) in soil consecutive irrigated with sewage effluent water for more than 50-years concentration. (M/L) as follows, Cd 2+ (1.61E-07), Ni 2+ ( 5.96E-07), and Pb 2+ (1.29E-08),they also added that continual use of sewage effluent in irrigation decreased the activity of both of Pb and Cd than the 0-yrs by ( 26% and 72%, respectively ), meanwhile Cd 2+ activity increased by about 8 times due to sewage effluent application.…”
Section: -Measurement CD Activities In the Tested Soilssupporting
confidence: 92%
See 2 more Smart Citations
“…The influences of soil contamination on the activities of Cd 2+ in soils were also investigated in the present study,as shown from the Table (3), pCd 2+ values were 9.08 and 8.09 in the 0-yrs and 100-yrs soil samples, respectively, indicating that the continual use of sewage effluent water in irrigation increased Cd 2+ activity by 9.94 folds than the control soil sample.These results are consistent with results reported by [11] who computed the activity of some metals (M/L) in soil consecutive irrigated with sewage effluent water for more than 50-years concentration. (M/L) as follows, Cd 2+ (1.61E-07), Ni 2+ ( 5.96E-07), and Pb 2+ (1.29E-08),they also added that continual use of sewage effluent in irrigation decreased the activity of both of Pb and Cd than the 0-yrs by ( 26% and 72%, respectively ), meanwhile Cd 2+ activity increased by about 8 times due to sewage effluent application.…”
Section: -Measurement CD Activities In the Tested Soilssupporting
confidence: 92%
“…This suggested that other possible solid phase of cadmium may be controlling its activity in that soil. They added that No known Cd mineral has yet been identified whose solubility, reflecting low activity of Cd 2+ .Meanwhile , [11] The data show that the solubility of Cd 2+ in virgin soil was closed to the solubility of CdCO3 (log CO2=-2.52) and CdSO4-2Cd(OH)2 at (log SO4=-2) , while in sludge soil ,the value of Cd 2+ was under saturated with respect the constructed Cd minerals. Cd 3 (PO 4 ) 2(logSO4=4.5)…”
Section: -Measurement CD Activities In the Tested Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides little indication of metal's bioavailability, mobility, and reactivity in soils, particularly soils treated with wastewater, sludge, and other organic fertilizers [3,4]. Therefore, it has been established that in most circumstances, the concentration of free ions (or activity) is the key factor in determining metal bioavailability and toxicity [1,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…2023, 8(2), 233-239 234 (or activity). The diagrams also allow some prediction of which solid phase regulates metal activity in the soil solution [6,7,17].…”
Section: Introductionmentioning
confidence: 99%